2017
DOI: 10.1002/1873-3468.12532
|View full text |Cite
|
Sign up to set email alerts
|

Differential requirement for N‐ethylmaleimide‐sensitive factor in endosomal trafficking of transferrin receptor from anterograde trafficking of vesicular stomatitis virus glycoprotein G

Abstract: Edited by James Rothman N-ethylmaleimide-sensitive fusion factor (NSF) is an ATPase that plays a crucial role in vesicular transport. Here, we examined the effects of NSF knockdown on Golgi structure and different vesicle trafficking pathways in mammalian cells. NSF knockdown caused Golgi fragmentation and abolished transferrin receptor exocytosis, defects that were rescued by RNAi-resistant NSF. Strikingly, NSF deficiency in HeLa cells barely affected cell viability, anterograde trafficking of vesicular stoma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…A previous study of HeLa cells after knockdown of NSF suggested that although endocytosis itself was unimpaired, the ability of cells to recycle endocytosed receptors back to the cell surface was blocked by the absence of NSF (11). We recapitulated these findings in HK2 cells using fluorescently labeled dextran as a marker for fluid phase bulk endocytosis and labeled transferrin as a marker for receptormediated endocytosis.…”
Section: Depletion Of Lrrk2 and Nsf Impairs Trafficking Of Endocytic Cargomentioning
confidence: 73%
See 1 more Smart Citation
“…A previous study of HeLa cells after knockdown of NSF suggested that although endocytosis itself was unimpaired, the ability of cells to recycle endocytosed receptors back to the cell surface was blocked by the absence of NSF (11). We recapitulated these findings in HK2 cells using fluorescently labeled dextran as a marker for fluid phase bulk endocytosis and labeled transferrin as a marker for receptormediated endocytosis.…”
Section: Depletion Of Lrrk2 and Nsf Impairs Trafficking Of Endocytic Cargomentioning
confidence: 73%
“…The former role depends upon its ATPase activity, whereas the latter occurs independent of its known enzymatic function. Cellular depletion of NSF in epithelial cells promotes Golgi fragmentation and defects in receptor recycling, though it has little effect on cell viability or endocytosis (11). Given the defects seen in LRRK2-deficient HK2 cells, these data suggested a functional link between NSF and LRRK2 in renal epithelia.…”
Section: Depletion Of Lrrk2 In Human Renal Epithelial Cells Promotes Vesicular Accumulationmentioning
confidence: 84%
“…ALK is considered a lung cancer-driven gene, but it was little reported in spindle cell sarcoma.ALK inhibitors are widely used in cancer-targeted therapy now, while the sensitivity to ALK inhibitors of different ALK fusion forms is different. NSF (N-ethylmaleimide sensitive factor) gene is a novel ALK fusion partner in translocation-associated neoplasia which is an ATPase that plays a crucial role in vesicular transport 16 .This is the rst study to describe a novel NSF-ALK fusion that may have promising e cacy by crizotinib treatment. In addition, next generation sequencing can provide more molecular change information and also give patients more therapeutic chance.…”
Section: Discussionmentioning
confidence: 99%
“…An intriguing candidate is NSF, an ATPase involved in vesicular transport and is implicated in having a role in learning, cognition, and memory. It has also been associated with schizophrenia through differential gene expression analysis done in prefrontal cortex and is located in a CNV, also including LRRC37A, LRRC37A2, ARL17A, ARL17B, associated with both dyslexia disorder and Parkinson's disorder ( Figure 7B) (Fan et al, 2017;Latourelle, Dumitriu, Hadzi, Beach, & Myers, 2012;Mirnics, Middleton, Marquez, Lewis, & Levitt, 2000;Veerappa, Saldanha, Padakannaya, & Ramachandra, 2014). Another interesting candidate is RNF123, a ubiquitin ligase involved in cell cycle progression found to be overexpressed in the cortex of patients with psychotic depression (Teyssier, Rey, Ragot, Chauvet-Gelinier, & Bonin, 2013).…”
Section: Intracranial Volume Twasmentioning
confidence: 99%